Comparison of Risk Scores for Predicting Outcomes in Patients with Hematologic Emergency - Sihombing, Benny (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
Hematologic emergencies are critical conditions that require rapid and accurate evaluation to determine the best management strategy. Various risk scores have been developed to predict patient outcomes in these situations, including the Sequential Organ Failure Assessment (SOFA), Acute Physiology and Chronic Health Evaluation (APACHE), and Hematologic Emergency Scoring System (HESS). This study aims to compare the effectiveness and accuracy of several risk scores in predicting mortality and morbidity in patients with hematologic emergencies. The method used is a retrospective study with data analysis from patients treated in the emergency unit with a critical hematologic diagnosis. The results show that the SOFA score has higher sensitivity compared to other scores in predicting patient mortality, while the APACHE score is superior in assessing long-term prognosis. The HESS score is specifically useful for evaluating patients with hematologic malignancies. The conclusion of this study is that selecting the appropriate risk score is crucial to improving the accuracy of outcome prediction and management of patients with hematologic emergencies.